REGULATORY AND LEGAL BASIS OF THE DIGITALIZATION OF THE PROFESSIONAL TRAINING OF TEACHERS IN HUNGARY - Olesia Stoika (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article examines the regulatory and legal basis of digitalization of professional training of teachers in Hungary. This study analyzes the legal framework for digitalization of teacher training in Hungary and the steps taken in the direction of digital transformation. Based on the analysis of regulatory documents and reports of the Hungarian government and the European Union, the works of Hungarian and domestic scientists, which directly highlight the topic of professional training of teachers, the digitalization of education, the necessary trends for further research into the digitalization of higher education in Hungary have been identified. To solve the tasks and achieve the goal of the research, a set of general scientific methods is used: theoretical: analysis and synthesis in order to determine the main directions of research into the problem of digitalization of professional training of teachers in Hungary; Empirical: study of the regulatory and legal framework regarding digitalization of professional training of teachers in Hungary; translation of authentic literature; description of factual information for the purpose of analytical interpretation and study of specific facts and phenomena; statistical processing of research results: for quantitative and qualitative data acquisition.As evidenced by the results of current studies of regulatory and legal documents, an urgent task for scientific research and educational policy in many European countries is to ensure the optimal use of the full potential of digital technologies for learning, while effective learning in the digital age becomes possible thanks to a systemic approach and holistic changes. Many European countries, including Hungary, are actively conducting research in the direction of full integration of digital technologies in education and vocational training.